SMART CITY PERSPECTIVES OF BLOEMFONTEIN, SOUTH AFRICA - Dillip DAS; Fidelise Emuze (Journal of Construction Project Management and Innovation)
To handle rapid urbanization, there is need to find new ways to manage complexity, increase efficiency, reduce expenses, and improve quality of life. The new ways are rooted in the concept of ‘smart city’. The concept theorize that emerging technologies would shape urban environments in varying ways that would include but not limited to the economy, mobility, governance, and living conditions of a city. While this concept is now a reality in major cities in developed economies, this is not the case in South Africa and the region. Against this background, an evaluation of socio-economic and environmental capital of Bloemfontein has been used as a case example to demonstrate the transformational requirements for a ‘smart city’ in South Africa. The evaluation utilised 74 indicators, and 30 factors of six smart characteristics, which include economy, environment, governance, living and mobility. Reviewed literature and semi-structure surveys were used for the evaluation, which suggests that Bloemfontein is lagging behind concerning key development indicators. In particular, the evaluation indicates that the city lag performance relative to mobility, economy, people and living sector, although environment and governance features appear to be promising. An overall evaluation of the indicators and factors points to a major scope for the city to transform to a smart city, if plausible actions are taken